Effects of negative and positive bias voltages on turbulence characteristics in J-TEXT tokamak. (1st January 2023) - Zhang, Bo; Liu, Hai; Xu, Yuhong; Chen, Zhipeng; Cheng, Jun; Liu, Haifeng; Wang, Xianqu; Huang, Jie; Zhang, Xin; Tang, Changjian; Shao, Junren; Chen, Zhongyong; et al.
Abstract: The effects of positive and negative bias voltages on the turbulence characteristics in the edge plasmas of J-TEXT are studied using Langmuir probe arrays. The experimental results illustrate that the turbulent particle transport fluxes are suppressed in both positive and negative bias cases, while the suppression mechanisms are quite different. For positive bias (+300 V), long-range correlation (LRC) structures with frequencies of about 10–30 kHz are generated, which are beneficial for turbulent transport suppression. In the −300 V bias case, no LRCs appear, while a strong mean flow shear exists which can reduce the amplitudes of potential and density fluctuations and thus decrease the turbulent transport.